Comparative Study Between Mixed Culture of Schizosaccharomyces Pombe with Saccharomyces and Single Culture Saccharomyces on Wine End Product - Mulyono, Roselyn; Tania, Veren; Heryson, Robert; Felix, Kenny Roy; Ratnasari, Nanda Risqia (Indonesia International Institute for Life Sciences, 2022)
Wine industry has always been searching for a way to improve the quality of its produce. Lately, the trends of using mixed culture of yeast to improve the wine qualities in the wine industry are increasing. The aim of this systematic review is to determine whether or not the mixed culture of Schizosaccharomyces pombe and Saccharomyces cerevisiae actually improves the quality of the wine. Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines were used to conduct the systematic review, and studies performed from 2010-2020 were collected from the databases of MDPI, ScienceDirect, Semantic Scholar, and PubMed. A total of 54 studies are systematically reviewed in this paper. Pure fermentation of S.cerevisiae produced generally acceptable wine qualities with desirable amounts of ethanol and acceptable amount of secondary metabolites, however in recent findings S.cerevisiae cannot naturally degrade malic acid, leading to a too sour-taste wine. Meanwhile, pure fermentation of S.pombe results in the high production of polysaccharide, pyranoanthocyanin, glycerol, pyruvic acid, urease; reduction of malic acid and gluconic acid, altogether considered as desirable traits in wine production. Mixed fermentation with S.cerevisiae and proper strain selection of S.pombe are the solutions for the suppressed production of acetic acid, acetaldehyde, and acetoin, which are the undesirable compounds highly produced by Schizosaccharomyces. The hypothesis is proven to be true as mixed fermentation of S.cerevisiae and S.pombe results in enhanced wine quality, especially contributed by the compounds produced from S.pombe fermentation.